Apply Second Newton's Law to mass m1:
in the x direction
"m_1 \\cdot a=T-f_1=\\{ f_1=\\mu _1 \\cdot Fn_1 \\}=T-\\mu _1 \\cdot Fn_1 \\space (1)" in the y direction
"0=Fn_1 -m_1 \\cdot g \\space (2)" From (1) and (2):
"T = m_1 \\cdot a + \\mu_1 \\cdot m_1 \\cdot g \\space (3)" Apply Second Newton's Law to mass m2:
in the x direction
"m_2 \\cdot a \\cdot cos30^ \\circ=-T \\cdot cos30^ \\circ - f_2 \\cdot cos30^ \\circ + Fn_2 \\cdot sin30^ \\circ""f_2 = \\mu_2 \\cdot Fn_2 \\space \\rightarrow \\space m_2 \\cdot a =-T + Fn_2 \\cdot (1\/ \\sqrt{3} - \\mu_2) \\space (4)" in the y direction
"-m_2 \\cdot a \\cdot sin30^ \\circ=T \\cdot sin30^ \\circ + f_2 \\cdot sin30^ \\circ + Fn_2 \\cdot cos30^ \\circ - m_2 \\cdot g""-m_2 \\cdot a =T + Fn_2 \\cdot (\\sqrt{3}+\\mu_2) - 2 \\cdot m_2 \\cdot g \\space (5)" From (4) and (5):
"-m_2 \\cdot a =T + (m_2 \\cdot a +T) \\frac {\\sqrt{3}+\\mu_2} {1\/ \\sqrt{3} - \\mu_2} - 2 \\cdot m_2 \\cdot g""a=\\frac g {m_1+m_2} \\Big( \\frac {m_2} {2} (1-\\sqrt{3} \\cdot \\mu_2)-\\mu_1 \\cdot m_1 \\Big)""a=\\frac {9.81 m\/s^2} {3 kg+4 kg} \\Big( \\frac {4 kg} {2} (1-\\sqrt{3} \\cdot 0.1 ) - 0.3 \\cdot 3kg \\Big) \\cong 1.06 \\frac {m} {s^2}" From (3):
"T = m_1 \\cdot a + \\mu_1 \\cdot m_1 \\cdot g = 3kg \\cdot 1.06 m\/s^2 + 0.3 \\cdot 3kg \\cdot 9.81 m\/s^2 \\cong 11.997 N" Answer:
"T \\cong 12 N ,\\space \\space a \\cong 1m\/s^2"
Comments
Leave a comment